Preschool education in Polish rural areas during economic transition - Matuszczak, Anna (Progress in Economic Sciences; No 1 (2014): Progress in Economic SciencesDO - 10.14595/PIES/01/013)
In this article the issue of preschool education in rural areas inPolandis compared to the situation in cities  and more  generally in the country. Analysis over a long period (from the beginning of the transformation) allowed for an indication of the trend of the studied phenomenon. The initial stress was on the importance of education at the youngest age, which is the base of human capital in any society. Then the level and dynamics of the number of pre-school and enrolled children in the previously approved subdivision was traced. The article concludes with an indication of the barriers to universal access to a kindergarten for children in rural areas, based on data acquired from the case study of a dozen farms.